Avaliação de perfis de imunossenescência em células do sangue periférico de pessoas vivendo com HIV (PVHIV) - Yuppiel Franmil Martinez (2018)
Immunosenescence changes are occurring in PLWH much earlier than in nonHIV infected individuals. The most notable changes happen in the adaptive immune system, especially in the T cell compartment. This study aims to assess the profiles of immunosenescence and exhaustion of circulating CD4+ and CD8+ lymphocytes in PLWH, as well as the possible correlation between immunosenescence profiles and absolute values and percentages of T CD4 lymphocytes at time zero and sixty months after. The immunosenescence and exhaustion were evaluated by flow cytometry through the expression of cell surface markers: CD45RA, CD27, CD28, CD57, CD62L, CCR7, CD95/Fas and programmed death-1 (PD-1). Samples were collected from 46 PLWH on follow up at a Reference Center for Infectious and Parasitic Diseases (Centro de Treinamento e Referência e Doenças Infecciosas e Parasitarias-Orestes Diniz) in Belo Horizonte, Brazil. Another 20 HIV seronegative individuals were included as a control group. PLWH were divided into three groups according to laboratory profiles in: slow progressors (SP), active replication (AR) and HAART with success. All subjects signed an informed consent form and this project was approved by the Institutional Research Ethics Committee. Our findings show that when compared to HIV seronegative individuals, PLWH had a decrease in naïve cells, as well as higher frequency and expression of effector cells in intermediate and advanced stages of differentiation. However, differences were observed among the three groups: a) In the AR group we observed the majority of the immune changes; b) CD4 and CD8 Immunophenotypic changes were seen in patients from both the AR and HAART groups; c) In the SP group these changes occurred exclusively in the CD8 compartment. On the other hand, the presence of immunosenescence profiles were negatively correlated with T CD4 absolute values and percentages at time zero and sixty months after. In conclusion our results show an increase in CD4 and CD8 immunosenescence profiles in all groups of PLWH studied and the expansion of these terminally differentiated cells had also a negative impact in the CD4+ count at time zero and sixty months after. These findings may in part explain the harmful role of immunosenescence in the chronic HIV infection.